A mitigator in Mandarin: the sentence-final particle ba (吧) - Fang Hongmei; Hengeveld Kees (Open Linguistics, 2020)
It has been widely claimed in the literature that the sentence-final particle ba in Mandarin Chinese is a modal element. This article argues against this claim and shows that ba is an element that has a unified mitigating function with scope over the utterance as a whole. Using the framework of Functional Discourse Grammar (FDG), and more specifically its hierarchical, layered organization, the article provides several arguments that support this new classification of ba. First, ba, like mitigators in general, but unlike modal elements, can occur in sentences with different basic illocutions. Second, ba may co-occur with modal elements of all different subtypes and thus cannot be a modal element itself. Third, ba may occur in sentences in which the speaker is highly confident of the propositional content. Fourth, unlike modal elements, ba may occur in certain types of non-propositional utterances. And fifth, the position that ba occupies with respect to other sentence-final particles shows that it has scope over the utterance as a whole. After thus arguing for the status of ba as a mitigator, we show how the general mitigating function of ba can acquire the more specific mitigating effects that have previously been attributed to it in the literature.